Predatory Neo-Victorian Novels - Jilling, Krisztina (Hungarian Journal of English and American Studies, 2021)
Book review:Ho, Tammy Lai-Ming. Neo-Victorian Cannibalism: A Theory of Contemporary Adaptations. Palgrave Macmillan, 2019. 150 pages. ISBN 978-3-030-02558-8. Hb. €58.84.